MOBILISATION OF LOCAL OWN-SOURCE REVENUE IN EAST JAVA PROVINCE: (Study of Regency and City Regional Revenue Agency in East Java Province) - Firstyanto, Augy Ladyana; Nuswantara, Dian Anita (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2021)
The purpose of this research is to analyze the influence of the fiscal decentralization level, the form of government administration, and the regional leading sector to the level of Local Own-Source Revenue mobilization in regencies and cities in East Java Province in the period of 2014 – 2018. The chosen populations are regencies and cities that are registered in East Java Province in 2014 – 2018. Multiple Linear Regression Analysis is an analysis method that is used in this study, using the SPSS 23 software. This study finds that the fiscal decentralization level has an influence on the Local Own-Source Revenue mobilization level, while the form of government administration and the regional leading sector have no influence on the Local Own Source Revenue mobilization level.